2021
DOI: 10.13031/trans.14225
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Surface Water Pesticide Exposure Assessments for Ecosystem Protection

Abstract: HighlightsCrop protection and pest management programs continue to be integral for modern food production.Potential ecological impacts of pesticides must be assessed, and key mitigation practices adopted.Efforts are needed to advance surface water pesticide exposure assessments from field to landscape scales.Ensuring effective pesticide mitigation practices requires quantifying dynamic site-specific characteristics.Ecological assessments must improve prediction of adverse population and community-level outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…Correspondingly, this will also require additional field characterization experiments. However, we believe that the research community should commit to this improved representation of these dynamic riparian buffers (Fox et al, 2021), especially considering the contribution of preferential flow reported in this research.…”
Section: Research Implications For Flow and Transportmentioning
confidence: 98%
See 1 more Smart Citation
“…Correspondingly, this will also require additional field characterization experiments. However, we believe that the research community should commit to this improved representation of these dynamic riparian buffers (Fox et al, 2021), especially considering the contribution of preferential flow reported in this research.…”
Section: Research Implications For Flow and Transportmentioning
confidence: 98%
“…iparian buffers and vegetative filter strips are commonly used mitigation practices to limit the transport of sediment, nutrients, pesticides, bacteria, and other contaminants from upslope fields into receiving surface water bodies (Momm et al, 2019;Fox et al, 2021). Their effectiveness has been demonstrated to depend not on the physical characteristics of the riparian buffer or vegetative filter strip (i.e., width) but rather on the mechanisms of contaminant detention and retainment (Sabbagh et al, 2009;Yu et al, 2011Yu et al, , 2013Fox and Penn, 2013;Wu et al, 2014aWu et al, , 2014bMuñoz-Carpena et al, 2018b;Cole et al, 2020;Walton et al, 2020).…”
mentioning
confidence: 99%
“…Overall, critical factors that must be ensured to achieve an effective VFS include sheet flow into and through the VFS, proper area ratio of VFS to the contributing area, the location of VFS in a watershed, and VFS vegetation type and density. Width alone, without reference to the contributing area, soil property, hydrological and pesticide characteristics, location, or vegetation type and density, is not a good predictor of VFS effectiveness (Carluer et al, 2011; Chen et al, 2016; Fox et al, 2021; Prosser et al, 2020; Sabbagh et al, 2009).…”
Section: Vegetative Filter Strips As a Pesticide Mitigation Measurementioning
confidence: 99%
“…Las prácticas agrícolas que utilizan plaguicidas son complejos y presentan interacciones biológicas, humanas y físico-químicas importantes y a menudo desconocidas. Estas interacciones incluyen el clima y la hidrología, el tipo de suelo, la selección y el uso de las mejores prácticas de gestión, el destino y el transporte de los productos químicos, la tecnología de aplicación y la socio-economía del uso de la tierra (Fox et al, 2021).…”
Section: Delitos Ambientalesunclassified